2019
DOI: 10.2478/prolas-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wavelength of Light on Growth, Yield and Nutritional Quality of Greenhouse Vegetables

Abstract: All previous reviews of research on light-emitting diodes (LEDs) have been focused on how different light spectra generally influence plant yield and quality. There are no or almost no reviews on the effect of spectra on sugars or pigment concentration, or yield and growth etc. The role of visible light in food production, as in agriculture and horticulture, is obvious, as light drives photosynthesis, which is crucial for plant growth and development. Solid state lighting using LEDs represents a fundamentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Several researches showed that photosynthesis under a combination of red and blue light tends to be higher than under HPS lighting, but fruit yield is equal ( 12 ). Olle and Virsile ( 26 ) found that red LEDs enhance tomatoes yield and that underlines findings of our research that states that generally with higher addition of red waves increases yield. In similar opinion, Zhang et al ( 14 ) defines that even adding FR light in combination with red LEDs and HPSL increases total fruit number.…”
Section: Discussionsupporting
confidence: 89%
“…Several researches showed that photosynthesis under a combination of red and blue light tends to be higher than under HPS lighting, but fruit yield is equal ( 12 ). Olle and Virsile ( 26 ) found that red LEDs enhance tomatoes yield and that underlines findings of our research that states that generally with higher addition of red waves increases yield. In similar opinion, Zhang et al ( 14 ) defines that even adding FR light in combination with red LEDs and HPSL increases total fruit number.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, an increasing number of supplementary light technology using light emitting diodes (LEDs) has been used in agricultural production [17][18][19][20]. The improvement in the growth, yield, and quality of crops has been confirmed by many studies [6,[21][22][23]. In addition, different light qualities also had different effects on the growth of cucumber and pepper [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Light systems with LEDs (lightemitting diodes) have important advantages over traditional ones due to their spectral composition, durability, 6 wavelength specificity, low radiant heat, and energetic efficiency (Urrestarazu et al, 2016). LEDs are important lamp types because the concentration of the light spectrum they emit can be changed to provide plants at various developmental stages with the required light spectrum (Olle and Alsiòa, 2019). The quality effects of the light spectrum on the production features and the influence on the contents of bioactive compounds in lettuce are well-known (Ohashi-Kaneko et al, 2007;Samuolienė et al, 2017).…”
Section: Influence Of Environmental Conditions On the Quantity And Quality Of Microgreen Production In Hydroponic Systemmentioning
confidence: 99%
“…The quality effects of the light spectrum on the production features and the influence on the contents of bioactive compounds in lettuce are well-known (Ohashi-Kaneko et al, 2007;Samuolienė et al, 2017). The photoresponses of antioxidant compounds suggest that the photoprotective mechanism is stimulated by both light-dosedependent and wavelength-dependent reactions (Carvalho and Folta, 2016;Samuoliene et al, 2016) Lettuce growth is influenced by light colour (Table 2; Olle and Alsiòa, 2019). Far-red lighting increases the number of leaves, elongates the leaves, and promotes the growth of the lettuce, resulting in taller plants (Yuyao and Krishna, 2021).…”
Section: Influence Of Environmental Conditions On the Quantity And Quality Of Microgreen Production In Hydroponic Systemmentioning
confidence: 99%